Guide to the use of libraries and information sources - Gates, Jean Key (McGraw-Hill, 1994)
This book provides a comprehensive treatment of libraries, with emphasis on the many kinds of library materials and on the various services libraries have to offer. This edition includes updated coverage of library reference sources, as well as expanded coverage of computerized information retrieval systems and computer-related search strategies.